2018
DOI: 10.1161/jaha.117.008131
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variations in In‐Hospital Mortality and Use of Percutaneous Coronary Intervention Following Acute Myocardial Infarction in China: A Nationwide Cross‐Sectional Analysis

Abstract: BackgroundPrevalence of acute myocardial infarction (AMI) is increasing in China, and AMI has become a major cause of mortality; however, information is very limited about the nationwide geographic and hospital variation in in‐hospital mortality (IHM) and the use of percutaneous coronary intervention (PCI) after AMI.Methods and ResultsFrom the Nationwide Hospital Discharge Database of China, we identified 242 866 adult admissions with AMI in 2015 from 1055 tertiary hospitals. We used multivariable logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 51 publications
3
30
0
Order By: Relevance
“…57 In China, a nationwide database study that included 1055 tertiary hospitals showed an in-hospital mortality of 3.6% and a PCI utilization rate of 37.2% in patients with NSTEMI (corresponding rates in patients with STEMI were 5.1% and 47.8%, respectively). 55 The study identified wide variations in the rates of in-hospital mortality across geographical regions, and the rates were significantly lower in patients who received PCI than in those who did not. 55 Geographical variation in care may be due to the lack of availability of cardiologists, catheterization laboratories, and medical treatments in rural areas compared with urban areas.…”
Section: Patient Characteristicsmentioning
confidence: 96%
See 4 more Smart Citations
“…57 In China, a nationwide database study that included 1055 tertiary hospitals showed an in-hospital mortality of 3.6% and a PCI utilization rate of 37.2% in patients with NSTEMI (corresponding rates in patients with STEMI were 5.1% and 47.8%, respectively). 55 The study identified wide variations in the rates of in-hospital mortality across geographical regions, and the rates were significantly lower in patients who received PCI than in those who did not. 55 Geographical variation in care may be due to the lack of availability of cardiologists, catheterization laboratories, and medical treatments in rural areas compared with urban areas.…”
Section: Patient Characteristicsmentioning
confidence: 96%
“…55 The study identified wide variations in the rates of in-hospital mortality across geographical regions, and the rates were significantly lower in patients who received PCI than in those who did not. 55 Geographical variation in care may be due to the lack of availability of cardiologists, catheterization laboratories, and medical treatments in rural areas compared with urban areas. 60 For example, a study assessing outcomes in patients with acute MI in New South Wales, Australia, showed that patients with NSTEMI presenting to a rural hospital were 70% less likely to undergo cardiac revascularization than patients presenting to an urban hospital.…”
Section: Patient Characteristicsmentioning
confidence: 96%
See 3 more Smart Citations